Constructing the Meaning of Nanotechnology in the United States: A Socio-Linguistic Analysis of the New York Times Coverage, 1985–2004. Issue 1 (February 2014) - Weber, Ian
This study employed a content analysis approach to consider the coverage of nanotechnology reports in the New York Times from 1985 to 2004. Patterns and trends of discourse within the national newspaper in terms of political, economic, social, cultural and technological factors were examined using a socio-linguistic approach. Results from the analysis of 243 news articles show a significant rise in the number of reports in general, with a specific focus on political, economic and technological factors. Analysis revealed that the three categories not only increased in relation to the rise in the number of articles, but also tended to positively reinforce each other over time. The implications of these findings are significant in relation to how the media reports on nanotechnology and the social and cultural dimensions of technology during the critical start-up phases of the innovation. Furthermore, this study brings into focus the issues of transparency of risk and sustainability of future nanotechnology applications.